Patients carrying CYP2C8*3 have shorter systemic paclitaxel exposure - Marcath, Lauren A (Pharmacogenomics, 2019)
AIM: First, evaluate if patients carrying putatively diminished activity CYP2C8 genotype have longer paclitaxel exposure (e.g., time above threshold concentration of 0.05 μM [T(c >0.05)]). Second, screen additional pharmacogenes for associations with T(c >0.05). METHODS: Pharmacogene panel genotypes were translated into genetic phenotypes for associations with T(c >0.05) (n = 58). RESULTS: Patients with predicted low-activity CYP2C8 had shorter T(c >0.05) after adjustment for age, body surface area and race (9.65 vs 11.03 hrs, β = 5.47, p = 0.02). This association was attributed to CYP2C8*3 (p = 0.006), not CYP2C8*4 (p = 0.58). Patients with predicted low-activity SLCO1B1 had longer T(c >0.05) (12.12 vs 10.15 hrs, β = 0.85, p = 0.012). CONCLUSION: Contrary to previous publications, CYP2C8*3 may confer increased paclitaxel metabolic activity. SLCO1B1 and CYP2C8 genotype may explain some paclitaxel pharmacokinetic variability.